Effect of Variation of Catalyst Concentration in the Producing of Biodiesel from Crude Palm Oil using Induction Heater - Yunsari, Sandhy; Husaini, A; Rusdianasari, R (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2019)
Biodiesel is an alternative fuel for diesel engines produced by transesterification and esterification of vegetable oils or animal fats with short-chain alcohols such as methanol. The reaction requires a catalyst, which is generally a strong base, thus producing a new chemical compound called methyl ester. One of the most common sources of biodiesel feedstock is CPO (Crude Palm Oil). CPO production in Indonesia is very high at 30.2 million tons in 2016, but CPO prices are low. Biodiesel can be produced using conventional methods, this method is less efficient because of its very slow and inefficient heating resulting from the transfer of energy to materials that depend on the convection currents and the thermal conductivity of the reaction mixture) which causes researchers to use new methods of producing Biodiesel, that is by using induction heating method. An induction heater is a technology that has been applied both in industry and households. The weight of the catalyst used uses variations of 0.6; 0.8; 1.0; 1.2; 1.4 %. The analysis showed that for optimal catalyst weight of 1.4%, yield biodiesel of 83.94%, density of 0.875 gr/cm3, the viscosity of 5.78 cSt, and flash point >100 oC. The use of 1.4% catalyst concentration produced biodiesel product that has a high yield and according to SNI 7128: 2015